(untitled) (The Research of Medical Science Review, 2025)
Introduction: CRP has been shown to reflect systemic and vascular inflammation and to predict future cardiovascular events. Elevated levels of CRP are associated with higher risk of adverse outcomes in patients at risk. Objectives: To find the frequency of in-hospital outcomes of patients presenting with acute coronary syndrome and high serum CRP levels. Subjects & Methods: This descriptive case series study conducted at the Cardiology Unit of Khyber Teaching Hospital, Peshawar, over a six-month period. 233 patients of 18-70 years of age and either gender who presented with confirmed diagnosed cases of ACS (i.e. presented with typical chest pain and diagnosed with STEMI, NSTEMI or unstable angina according to our operational definition) and CRP levels more than 6mg/dL at the time of presentation were included in the study. All the selected patients were observed for the clinical in-hospital outcome till their discharge as per defined in operational definition. SPSS software version 25.0 will be used for data entry and analysis purpose. Results. 73.4% (n=171) patients were males while rest of the patients were female. Cumulative mean age was 58.23 years ± 19.95 SD. Mean Troponin levels and CRP levels were noted as 2.01±0.63 ng/ml and 13.55±3.95 mg/L respectively. It was observed that 67.4% (n=157) were discharged with stable condition, whereas 9.9% (n=23) died. Heart failure was the most frequently observed in-hospital outcome 18.9% (n=44). Our study revealed that no statistically significant association (p-value≤0.05) was noticed only for any of the effect modifier except troponin levels and CRP levels. Conclusions: Heart failure was noted as most frequent worst outcome followed by death and cardiogenic shock. No significant association was observed between in-hospital ACS outcomes and factors like ACS type, age, or gender. However, elevated CRP levels and troponin levels demonstrated statistically significant link to adverse in-hospital ACS outcomes.